(untitled) (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Echinacea purpurea is a flower that is rich in its main antioxidant content comes from flavonoids, phenols, and cystic acids can be utilized as an immunomodulator during the Covid-19 pandemic. Ekinase flowers are processed into new innovations in nutraceutical products with the Ekino Ice product label. Goal to innovate nutraceutical products made from dry flower Echinacea purpurea as immunomodulators in the era of the Covid-19 pandemic. This research uses laboratory experimental methods with a qualitative approach. Microscopic test results are known that the sample has a plant characteristic of Echinacea purpurea. KLT test results using UV 366 light is positive flavonoid blue color Rf 0.5 nm with ammonia stain appearance, positive phenol stain blue-black color Rf 0.75 nm with FeCl3 stain appearance, positive cystic acid stain blue color Rf 0.75 nm. Brown organoleptic test results, characteristic smell of Echinacea purpurea, and taste sweet. pH test result 6.42 and melting time test result 16.22 minutes. Ekino Ice has the potential to be a new innovation nutraceutical product as immunomodulators in the era of the Covid-19 pandemic.